African Continental Free Trade Area (AfCFTA) Agreement and the Mega-Regional Trade Agreements (MRTAs): what are the underlying challenges and prospects for Africa-South-South trade? - Anayochukwu Basil Chukwu; Tobechi Agbanike; Lasbrey Anochiwa (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This study examines the possible challenges and prospects of the recent signing of the African Continental Free Trade Area (AfCFTA) Agreement on South-South trade. The recent ratification of the agreement by the African Union (AU) Heads of Government and the establishment of the mega-regional trade agreements (MRTAs) by the major global trading economies are the biggest since the establishment of the WTO. One of these regional and continental agreements' principal objectives is to further strengthen trade terms and balance of trade statistics between member nations. Whereas almost all the regional and continental blocs have to a large extent, achieved the purpose of their trade agreements, Africa stands out as the only region whose intra-trade value still constitutes less than 15% of global trade share. Many reasons have been adduced to be responsible for the weak trade performance, one of which is weak regional integration. This study, therefore, concludes that for Africa to achieve significant improvement in global trade, the region needs to encourage regional trade, which will act as a catalyst for transforming the domestic economies and lay a robust foundation for healthy regional competition and integration